EDUKASI SUPORTIF TENTANG FAKTOR PENCETUS KECEMASAN IBU HAMIL MASA PANDEMI COVID 19 DAN UPAYA MENGATASI DI KELURAHAN BANDAR LOR KOTA KEDIRI - Triatmi Andri Yanuarini; Sinta Kristianti; Finta Isti Kundarti; Dwi Estuning Rahayu (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2022)
The COVID-19 pandemic has doubled the number of women reaching abnormal levels of anxiety. The prevalence of anxiety disorders during pregnancy, in developed and developing countries is 10% and 25%, respectively. Anxiety during pregnancy, if not prevented, will lead to problems during labor and postpartum, such as abortion, preterm (premature) labor, and even postpartum depression. One of the efforts to reduce the anxiety of pregnant women during a pandemic is to provide appropriate information regarding screening for anxiety triggers so that cadres and pregnant women can detect them as early as possible. The purpose of this community service is to increase the knowledge of pregnant women about screening for anxiety trigger factors in pregnant women during the Covid-19 pandemic and efforts to overcome them. The community service method is carried out by inviting pregnant women and cadres to be given supportive education about the triggers for anxiety in pregnant women during the Covid 19 pandemic and efforts to overcome them. Before being given the material, a pre-test was carried out and after the material was given a post-test was carried out. The results of the pre test obtained 4% of good cadre knowledge, for post test 72% of good cadre knowledge. As for pregnant women, the results of the pre test obtained as much as 52% experienced anxiety in the very severe category. After being given the material, pregnant women with anxiety in the very severe category were reduced to 32%.